PENERAPAN TEORI KENDALI PADA MASALAH PROGRAM DINAMIK - Pardi Affandi; Dewi Anggraini; Nur Salam (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2012)
This study examines the application of Control Theory to the problem of Dynamic Program. Dynamic program is a design analysis in math to determine a series decisions relating to the decision-making process are gradually double to optimize problem solving effectively. Classic problems in dynamic programming is the concept of phase, state and acquisition. Problem solving will use Control Theory.